Production Variability and Categorical Perception of Vowels Are Strongly Linked - Chao, Sara-Ching; Ochoa, Damaris; Daliri, Ayoub (Frontiers in Human Neuroscience, 2019)
Theoretical models of speech production suggest that the speech motor system uses auditory goals to determine errors in its auditory output during vowel production. This type of error calculation indicates that within-speaker production variability of a given vowel is related to the size of the vowel’s auditory goal. However, emerging evidence suggests that the speech motor system may also take into account perceptual knowledge of vowel categories (in addition to auditory goals) to estimate errors in auditory feedback. In this study, we examined how this mechanism influences within-speaker variability in vowel production. We conducted a study (n = 40 adults), consisting of a vowel categorization task and a vowel production task. The vowel categorization task was designed—based on participant-specific vowels—to estimate the categorical perceptual boundary between two front vowels (/ɛ/ and /æ/). Using the vowel production data of each participant, we calculated a variability-based boundary located at the “center of mass” of the two vowels. The inverse of the standard deviation of a vowel distribution was used as the “mass” of the vowel. We found that a) categorical boundary was located farther from more variable vowels, and b) the calculated variability-based boundary (i.e., the center of mass of the vowels) significantly and positively correlated with the estimated categorical boundary (r = .912 for formants calculated in hertz; r = .854 for formants calculated in bark). Overall, our findings support a view that vowel production and vowel perception are strongly and bidirectionally linked.